Deep Backgrounds: Landscapes of Labor in All the President’s Men (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
Although commonly understood as journalistic thriller tied to the historical realities of the Watergate investigation, Alan J. Pakula’s All the President’s Men is deeply imbricated in contemporaneous ideas about office design and white collar labor. Drawing on the film’s production history, as well as discourses around knowledge work, office furnishings, and the changing role of paper in office work, this essay places All the President’s Men along a different historical trajectory, one in which Hollywood cinema elaborates, expressively re-stages, and fantasizes the white-collar workspace.
Keywords: Alan J. Pakula; All the President'sMen; 70s; workspace